Repair Integrity and Re-tear Pattern after Arthroscopic Suture-Bridge Rotator Cuff Repair Abbreviating Medial-row Knot-tying. Issue 7 (29th July 2019) - Takeuchi, Yasutaka; Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuke; Tokai, Morihito; Morioka, Takeshi; Ueda, Yusuke; Hamada, Hiroshige
Objectives: Recently suture bridging technique has become the most popular footprint reconstruction procedure, and many surgeons prefer to perform lateral row fixation after tying the medial-row suture. According to some authors, strangulation caused by medial-row knot can lead to re-tear at the muscle-tendon junction, which is called type II failure. They have reported type II failure occurred 59˜74% in re-tear cases with conventional suture bridging. In order to avoid stress concentration on the medial-row, we prefer to use triple-loaded suture anchors for the medial-row, and perform lateral-row fixation of suture bridging before tying medial-row suture. This is a procedure in which we reduce the cuff to the tuberosity first, then press down the cuff to the footprint by tying the remaining suture. The purpose of this study was to assess the functional outcomes and structural integrity after our suture bridging technique. Methods: From April 2012 to May 2015, a consecutive series of 373 patients (4 bilateral cases) with complete rotator cuff tear were performed arthroscopic rotator cuff repair in our hospital. There were 90 small, 135 medium, 117 large, and 35 massive tears according to Cofield classification. Functional outcomes were assessed using JOA and UCLA score preoperatively and at final follow-up which was 29 months on average after surgery. Repair integrity was evaluated with MRI performed at a mean of 14 months after surgery and was graded using Sugaya classification. In addition, re-tear was divided into 2 groups. Type I failure is detachment from the footprint (group F1). Type II failure is muscle-tendon junction failure (group F2). We also investigated the relationship between clinical outcomes and repair integrity/tear pattern. Statistical analysis was performed using paired t test for comparing clinical outcomes and one-factor ANOVA/Tukey-Kramer test or Kruskal-Wallis test/Steel Dwass test to compare difference between the groups. Results: Regarding clinical outcomes, both JOA and UCLA scores have significantly improved overall from 72 to 95 and 18 to 34, respectively (P <0.0001). Postoperative MRI demonstrated successful repair in 318 shoulders (84.4%: group S) and re-tear (Sugaya type IV and V) in 59 shoulders (15.6%). There were 16 re-tears (7.1%) in small to medium tears and 43 re-tears in large and massive tears (28.3%). Among 59 re-tears, 39 shoulders (66%) were type I failures (group F1) and 20 shoulders (34%) were type II failures (group F2). Postoperative JOA score was significantly improved in both successful and failed repairs: 72 to 95 in group S, 72 to 94 in group F1 and 70 to 91 in group F2 (P <0.0001). Although preoperative scores demonstrated no significant difference between 3 groups, postoperative scores were significantly different between group S and group F2 (P=0.0008) and group F1 and group F2 (P=0.027). Similarly, postoperative UCLA score in group F2 was also significantly inferior to group S (p=0.0008) and group F1 (P =0.036). Conclusion: Our suture bridging technique abbreviating medial-row knot tying demonstrated excellent functional outcomes and structural integrity after surgery. In addition, rate of muscle-tendon junction failure, which proved to be functionally deteriorated compared with type I failure, was obviously lower when compared with previous reports with conventional suture bridging.